Low-Temperature Aqueous Batteries: Challenges and Opportunities. Issue 3 (1st March 2022) - Sui, Yiming; Yu, Mingliang; Xu, Yunkai; Ji, Xiulei
Abstract : Aqueous batteries represent promising candidates to address the grand challenge of energy storage. Ideally, a battery ought to deliver performance at low temperatures. Unfortunately, pure water has a high freezing point of 0 °C at 101 KPa, where the limited low-temperature performance of aqueous batteries is usually expected. However, significant progress has been made recently in suppressing the freezing point of aqueous electrolytes, which leads to the demonstration of some low-temperature aqueous batteries. This article summarizes the challenges in low-temperature aqueous batteries as well as the reported strategies in promoting the low-temperature performance of these batteries.